Becoming a Distance Manager: Managerial Experiences, Perceived Organizational Support, and Job Satisfaction During the COVID-19 Pandemic - Ipsen, Christine; Kirchner, Kathrin; Andersone, Nelda; Karanika-Murray, Maria (Frontiers in Psychology, 2022)
Due to the COVID-19 pandemic having radically changed the way we now work, many recent studies have focused on employees’ experiences and well-being, their performance and job satisfaction (JSA), and ways to ensure the best support for them when working from home (WFH). However, less attention has been given to managers’ experiences in adapting to the new role of distance management and supporting them with this transition. This study aims to explore how managers experienced distance management, and the perceived organizational support (POS), and the effect of organizational support has on their JSA during the first year of the COVID-19 pandemic. Data from 1,016 line, middle and top managers in Danish workplaces were collected in March 2021, 1 year after the start of the COVID-19 pandemic. We applied descriptive statistics, ANOVA, and partial least square structural equation modeling to investigate the relation of perceived organizational support (POS) and the JSA of distance managers. Control variables were the respondents’ demographic characteristics, specifically gender, age, and management level. The study offers insights into the managerial experiences of becoming a distance manager, helps to understand the relationship between POS and managers’ JSA, and shows a positive relationship similarly for the managers as for employees. The study shows that most managers found their work as distance managers more demanding and worked more hours. The data demonstrate that managers received the most support from their own employees and manager peers, whereas administrative support was largely lacking. The data also show that the majority (67%) of the managers prefer to manage from the office, but similarly, they can continue managing from a distance if needed post-pandemic. The study adds to the literature on workplaces’ transitioning to distance management and hybrid work and contributes to understanding the role of POS and managers’ JSA during this transition. Consequently, if an organization aims to offer hybrid work, improving support from top management and in-house support functions would help maintain or increase managers’ JSA.